THE THEORETICAL FOUNDATIONS OF THE FORMATION OF FINANCIAL MECHANISMS FOR ATTRACTING FOREIGN INVESTMENT (American Journal of Business Management, Economics and Banking, 2025)
The article reveals the financial mechanisms for effectively attracting foreign investment into the economy: methods, forms, management tools and financial instruments for effectively attracting foreign investment. As a result of the research, the author’s conclusion on the financial mechanism for attracting foreign investment is formed, conclusions and recommendations are given.